Demencia frontotemporal y manía: estudio de un caso y revisión de la literatura - Sánchez González, Roberto; López Zumeta, Silvia; Almendrote Muñoz, Miriam; Prats Sánchez, Luis (Revista Cubana de Neurología y Neurocirugía, 2013)
INTRODUCTION: Frontotemporal Dementia is a descriptive term used to define a dementia invariably associated with degeneration of the frontal and temporal lobes, in the absence of Alzheimer's disease. It is a heterogeneous group of neurodegenerative diseases with different clinical manifestations, genetic component and anatomopathological alteration. It´s psychiatric symptoms have an insidious onset, with personality deterioration and progressive affectation of behavior. Usually these changes occur before finding abnormalities in neuroimaging studies, their characteristics depend on the location of the cerebral lesions and usually are precede or mask by cognitive disabilities. Apathy and lack of volition are common initial symptoms and occurs in most patients as the disease progresses. Disinhibition is manifested by inappropriate social behaviors such as inadequate laughter, exhibitionism, restless, impulses, uncontrolled sexuality and violence, inappropriate jocularity and childish humor; that symptoms can be present in a half of patients. CASE REPORT: A representative case report was considered in which the first manifestation of dementia is a syndrome with manic features. Also, specific literature published to date is reviewed. CONCLUSIONS: Is required a correct differential diagnosis between dementia and the beginning of a late onset bipolar affective disorder, and complementary examinations can be useful for this purpose.